Морфологічна характеристика Cleome spinosa Jacq. (Сleomaceae) та її селекційних форм, інтродукованих у Національному ботанічному саду ім. М.М. Гришка НАН України - Mashkovs'ka, S.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
The detail morphological description of vegetative and generative plants' organs of Cleoma spinosa Jacq and its 4 selection forms (Alba, Purpurea, Rosea, Violaceae) is introdused, which were selected as the most perspective for engaging to selection activity. The morphological characteristics can be used in a systematics and phylogeny, at compiling polytomic keys, for seeds and fruits identification of the selection forms Cleome spinosa, and also in selection activity.